(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The experiment was carried out at the Field Laboratory, Department of Environmental Science, Bangladesh Agricultural University, Mymensingh during the period of March, 2012 to July, 2012 to evaluate the effect of fertilizer and manure on the growth and yield of Tulsi and Pudina. There were six treatments consisting of control (No fertilizer and manures), cowdung, poultry manure, cowdung+ NPK fertilizer, poultry manure+ NPK fertilizer and Mixed fertilizer. All the treatment significantly influenced most of the growth and yield components of Tulsi and Pudina. The plant height, No. of branch/plant, No. of leaf/plant, Leaf length, 1000- fresh leaf weight and fresh yield were highest where cowdung was applied. All the above parameters were lowest where no manures were applied (control). From these results it was clear that cowdung was the best for soil quality and growth and yield of Tulsi and Pudina medicinal plant. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22197 J. Environ. Sci. & Natural Resources, 7(2): 13-16 2014